Pengaruh Brand Equity Terhadap Purchase Intention Produk Es Krim Cornetto Disc Oreo pada Masyarakat Kecamatan Medan Sunggal - Hasman, Haryaji Catur Putera; Saputri, Ayumi Yukiko; Suryani, Wan (Peneliti.net, 2024)
This research aims to test and analyze the influence of brand equity on purchase intention for Cornetto Disc Oreo ice cream products in the Medan Sunggal District Community. This type of research is quantitative and associative research. This research consists of one independent variable and one dependent variable. The independent variable in this research is Brand equity (X) and the dependent variable is Purchase intention (Y). The sampling technique used was a purposive sampling method with the criteria being that respondents were over 17 years old, people who live in Medan Sunggal District, and people who know the Cornetto Disc Oreo ice cream product. The sample in this study was 100 respondents. The data collection technique uses a survey method via questionnaires. The results of this research resulted in the finding that the brand equity variable had a positive and significant effect on purchase intention for Cornetto Disc Oreo ice cream products in the Medan Sunggal District Community.